Encapsulation of graphene transistors and vertical device integration by interface engineering with atomic layer deposited oxide. (1st December 2016) - Alexander-Webber, Jack A; Sagade, Abhay A; Aria, Adrianus I; Van Veldhoven, Zenas A; Braeuninger-Weimer, Philipp; Wang, Ruizhi; Cabrero-Vilatela, Andrea; Martin, Marie-Blandine; Sui, Jinggao; Connolly, Malcolm R; Hofmann, Stephan
Abstract: We demonstrate a simple, scalable approach to achieve encapsulated graphene transistors with negligible gate hysteresis, low doping levels and enhanced mobility compared to as-fabricated devices. We engineer the interface between graphene and atomic layer deposited (ALD) Al2 O3 by tailoring the growth parameters to achieve effective device encapsulation whilst enabling the passivation of charge traps in the underlying gate dielectric. We relate the passivation of charge trap states in the vicinity of the graphene to conformal growth of ALD oxide governed by in situ gaseous H2 O pretreatments. We demonstrate the long term stability of such encapsulation techniques and the resulting insensitivity towards additional lithography steps to enable vertical device integration of graphene for multi-stacked electronics fabrication.